The Effect of Cognitive Diagnostic Assessment and Non-Cognitive Diagnostic Assessment on Social Studies Learning Motivation of Grade VIII Students at UPT SMPN 2 Binamu, Jeneponto Regency - Mantasiah, Mantasiah; Syarifuddin, Syarifuddin; Fahreza W, Muhammad (International Forum of Researchers and Lecturers, 2025)
This study aims to determine and analyse 1). The effect of cognitive diagnostic assessment on the social studies learning motivation of eighth-grade students at UPT SMPN 2 Binamu, Jeneponto Regency. 2). The effect of non-cognitive diagnostic assessment on the social studies learning motivation of eighth-grade students at UPT SMPN 2 Binamu, Jeneponto Regency. 3). The simultaneous influence of cognitive diagnostic assessment and non-cognitive diagnostic assessment on the social studies learning motivation of eighth-grade students at UPT SMPN 2 Binamu, Jeneponto Regency; and 4). To determine and analyse the dominant variables that influence the social studies learning motivation of eighth-grade students at UPT SMPN 2 Binamu, Jeneponto Regency. This research uses a quantitative research approach. The research was conducted on eighth-grade students at SMPN 2 Binamu, Jeneponto Regency, with a population consisting of all eighth-grade students at SMPN 2 Binamu, Jeneponto Regency, comprising five classes, namely: VIII 1, VIII 2, VIII 3, VIII 4, and VIII 5, with a total of 154 students. The sampling technique used was purposive random sampling, with 10 students representing each class, resulting in a sample size of 50 students. Data collection was conducted using questionnaires, and data analysis was performed using multiple regression analysis, t-test, and F-test. The results of the study are as follows: 1) Cognitive Diagnostic Assessment (X1) has a positive and significant effect on the social studies learning motivation of eighth-grade students at UPT SMPN 2 Binamu, Jeneponto Regency. 2) Non-cognitive Diagnostic Assessment (X2) has a positive and significant effect on the social studies learning motivation of eighth-grade students at UPT SMPN 2 Binamu, Jeneponto Regency. 3). Cognitive Diagnostic Assessment (X1) and Non-Cognitive Diagnostic Assessment (X2) together have an effect on Social Studies Learning Motivation (Y) among eighth-grade students at UPT SMPN 2 Binamu, Jeneponto District. 4). The most dominant variable influencing the social studies learning motivation of eighth-grade students at UPT SMPN 2 Binamu, Jeneponto District, is cognitive diagnostic assessment.